Influence of Image Acquisition on Radiation Dose and Image Quality: Full versus Narrow Phase Window Acquisition Using 320 MDCT - Faisal Khosa; Atif Khan; Khurram Nasir; Waqas Shuaib; Matthew Budoff; Ron Blankstein; Melvin E. Clouse (The Scientific World Journal)
Purpose. To compare radiation dose and image quality using predefined narrow phase window versus complete phase window with dose modulation during R-R using 320-row MDCTA. Methods. 114 patients underwent coronary CTA study using 320-row MDCT scanner. 87 patients with mean age (61 + 13 years), mean BMI (29 + 6), and mean heart rate (HR) (58 + 7 bpm) were imaged at predefined 66–80% R-R interval and then reconstructed at 75% while 27 patients with mean age (63 + 16 years), mean BMI (28 + 5), and mean HR (57 + 7 bpm) were scanned throughout the complete R-R interval with tube current modulation. The effective dose (ED) was calculated from dose length product (DLP) and conversion k (0.014 mSv/mGy/cm). Image quality was assessed using a three-point ordinal scale (1 = excellent, 2 = good, and 3 = nondiagnostic). Results. Both groups were statistically similar to each other with reference of HR (P=0.59), BMI (P=0.17), and tube current mAs (P=0.68). The median radiation dose was significantly higher in those scanned with complete R-R phase window versus narrow phase window (P<0.0001). Independently of patient and scan parameters, increased phase window was associated with higher radiation dose (P<0.001). Image quality was better among those scanned with narrow phase window versus complete phase window (P<0.0001). Conclusion. Our study supports that good HR control and predefined narrow window acquisition result in lower radiation dose without compromising diagnostic image quality for coronary disease evaluation.